STRATEGI KOMUNIKASI PEMBERDAYAAN MASYARAKAT (STUDI PADA KELOMPOK USAHA DAPUR PESISIR OLEH PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) KABUPATEN KEPULAUAN MERANTI) - Tegar, Muhammad; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Family Income Improvement Business or commonly referred to as UP2K is one of the work programs in the Tim Penggerak PKK of Kepulauan Meranti Regency. The Work Program is one of the efforts of the Tim Penggerak PKK of Kepulauan Meranti Regency to help improve the economy of the community, especially the people of Kepulauan Meranti Regency. One of their program targets is the Dapur Pesisir UP2K Group which processes lomek fish into nuggets. Therefore this study aims to find out the community empowerment communication strategy of the Tim Penggerak PKK of Kepulauan Meranti Regency, how to implement the community empowerment communication strategy and how the evaluation process and the factors that influence the community empowerment communication strategy carried out by PKK Kepulauan Meranti Regency.This study uses a descriptive qualitative research method and uses the participatory communication model of Lawrence Kincaid and Everett M. Rogers. The research subjects were 10 informants who were selected using purposive and incidental techniques. Data collection is done through in-depth interviews, observation and documentation. To do data validity, the author uses triangulation and extension techniques.The results of this study indicate that the community empowerment strategy has gone well. The Community Empowerment Communication Strategy that has been carried out by the District PKK is through several stages. First is the communication infrastructure (hardware). The second is the planning of a communication program (software). After that, the implementation of the community empowerment communication strategy is seen from participation with the stages of providing information, consultation, decision making together, acting together, supporting (supporting independent community interest). The implementation of the community empowerment communication strategy that was carried out by the PKK Kepulauan Meranti district together with the agencies that cooperated with the UP2K program, namely by providing socialization, guidance (discussions, UP2K strengthening training, UP2K competition and assessment, administrative training and bookkeeping) monitoring, facilitator, POM permit, product packaging training and also providing assistance in the form of funds and equipment procurement. The communication model used by the Kepulauan Meranti PKK is the Kincaid Participatory Communication model.  Keywords: PKK, Dapur Pesisir, Empowerment Communication, Groups Business, Nugget